2005
DOI: 10.1038/sj.emboj.7600563
|View full text |Cite
|
Sign up to set email alerts
|

Processing of DNA for nonhomologous end-joining by cell-free extract

Abstract: In mammalian cells, nonhomologous end-joining (NHEJ) repairs DNA double-strand breaks created by ionizing radiation and V(D)J recombination. We have developed a cell-free system capable of processing and joining noncompatible DNA ends. The system had key features of NHEJ in vivo, including dependence on Ku, DNA-PKcs, and XRCC4/Ligase4. The NHEJ reaction had striking properties. Processing of noncompatible ends involved polymerase and nuclease activities that often stabilized the alignment of opposing ends by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 46 publications
8
110
0
Order By: Relevance
“…Although DNAs with cohesive ends have been used as substrates for in vitro NHEJ assays, such assays do not necessarily entail the action of the nuclease or polymerase characteristic of NHEJ (3,4,32,65), and alternative substrates have been devised (5,30,42). We generated a 5.7-kb DNA substrate with incompatible protruding 3Ј ends (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although DNAs with cohesive ends have been used as substrates for in vitro NHEJ assays, such assays do not necessarily entail the action of the nuclease or polymerase characteristic of NHEJ (3,4,32,65), and alternative substrates have been devised (5,30,42). We generated a 5.7-kb DNA substrate with incompatible protruding 3Ј ends (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies by the Chu lab (151) with fractionated cell extracts have shown that DNA ligase IV/XRCC4 is required for processing of DNA molecules with incompatible ends. This implies that DNA ligase IV/XRCC4 acts prior to and is necessary for the subsequent recruitment of end-processing activities, providing an explanation as to why DNA molecules with cohesive ligatable ends are predominantly joined without processing (152). Although Ku is required for the recruitment of DNA ligase IV/XRCC4 to double-strand breaks, there are contradictory reports as to the role DNA PK cs in this recruitment (153,154).…”
Section: Dna Ligase IVmentioning
confidence: 97%
“…NHEJ has been reconstituted using purified components from mammals (52) and yeast (16). More-extensive studies, to date limited to mammalian cells and Xenopus laevis, have examined DNA end joining in cell and nuclear extracts (47), where Ku-dependent NHEJ (4,12,14,17,42,46), as well as the other forms of end joining observed in vivo (14,17,32,46,50,60,67,73), can be seen.…”
mentioning
confidence: 99%